2021
DOI: 10.1007/s00382-021-05984-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of climate change on extreme temperature and precipitation events over the Kashmir Himalaya

Abstract: The frequency and severity of climatic extremes is expected to escalate in the future primarily because of the increasing greenhouse gas concentrations in the atmosphere. This study aims to assess the impact of climate change on the extreme temperature and precipitation scenarios using climate indices in the Kashmir Himalaya. The analysis has been carried out for the twenty-first century under different representative concentration pathways (RCPs) through the Statistical Downscaling Model (SDSM) and ClimPACT2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 91 publications
1
8
0
Order By: Relevance
“…The percentages of total frequency and volume contribution of four EEP patterns computed with IMD data are plotted in Figure 5. Here we used the inverse distance weightage (IDW) method as this interpolation method for smother representation of the results (Figures 5–14) as it is most appropriate and has been widely used in high altitude regions (Ahsan et al, 2022; Das et al, 2022; Saha et al, 2022). The percentage of the total frequency of TDP1 and TDP2 is similar (ranging between 30% and 40%).…”
Section: Resultsmentioning
confidence: 99%
“…The percentages of total frequency and volume contribution of four EEP patterns computed with IMD data are plotted in Figure 5. Here we used the inverse distance weightage (IDW) method as this interpolation method for smother representation of the results (Figures 5–14) as it is most appropriate and has been widely used in high altitude regions (Ahsan et al, 2022; Das et al, 2022; Saha et al, 2022). The percentage of the total frequency of TDP1 and TDP2 is similar (ranging between 30% and 40%).…”
Section: Resultsmentioning
confidence: 99%
“…The imprints of global climate change are well established from the observational datasets in the Jhelum basin and its impacts are already being felt (Ahsan et al, 2021a). Few studies e.g., (Ahsan et al, 2021b) have also attempted to estimate the magnitude of climatic changes over the 21 st century. However, these studies are limited in scope because the projections are based on a single GCM.It has been found that GCM outputs inherit considerable uncertainty in them and thus use of a single GCM can yield inaccurate results (Khan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, the tourism impacts and non-tourism activities on socio-cultural and environmental issues are hard to separate and evaluate (Briassoulis 2002 ). Mountain ecosystems like the Himalayas are especially susceptible to climate change owing to limited adaptive ability, resources, and cascade effects on downstream environments (Ahsan et al 2021 , p 0.2, Ahsan et al 2022 , p. 1665). The increased pressure on the population, commercial forestry, tourism activities, and economic prosperity are the leading causes of the destruction of the environment in the Himalayan ecosystem (Rawat and Sharma 1997 ).…”
Section: Literature Reviewmentioning
confidence: 99%